ANALYSIS OF DRUG COST TOWARD CAPITATION COST FOR TOP DISEASES IN SPECIAL REGION OF YOGYAKARTA PUBLIC HEALTH CENTERS - Satibi, Satibi; Pambudi, Risma Sakti; N, Trisnadewi; Wilonakaulika, Wilonakaulika; Diahayupuspandari, Diahayupuspandari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In this study wanted to analyze the differences between actual and standard of prescription cost. Researchers also conducted an analysis to see whether there was a difference between actual and standard of drug value in the amount of capitation fund. Methods: This study was a retrospective observational analytic. Medical prescriptions (January 2015–June 2015) will be obtained at several Puskesmas in D.I Yogyakarta. Mann–Whitney test was performed to conduct whether there was a difference between actual and standard of prescription cost. Independent sample t-test was performed to conduct whether there was a difference between actual and standard of drug value in the amount of capitation fund. Results: Based on the data, it showed that there was a significant difference (p<0.05) between actual and standard of prescription cost. There was also a significant difference between actual and standard of drug value in the amount of capitation fund at Puskesmas in Yogyakarta city and Bantul district. The difference of value caused by prescription cost value factor that there is duration component in calculation. Yet in Sleman district, there was no significant difference (p>0.05). Conclusion: There was a significant difference between actual and standard of prescription cost. There was also a significant difference between actual and standard of drug value in the amount of capitation fund at Puskesmas in Yogyakarta city and Bantul district. Yet in Sleman district, there was no significant difference.